(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Analysis of Marketing Channel on Grain in Singapadu, Gianyar. The marketing channel for paddy rice by farmers in Singapadu village, Gianyar, still relies on the intervention of middlemen. The "ijon" system, which is the main marketing channel, causes paddy rice prices to often fluctuate from high to very low. This results in farmers still being highly dependent on middlemen despite the inefficiency of the marketing channel through middlemen. The purpose of this research is to determine how the marketing channels for paddy rice from producers to consumers operate, and to conclude which marketing channel is the most efficient for farmers to choose. The analysis methods used in this research are quantitative and qualitative analyses with a descriptive approach. Research instruments used include interviews, surveys, and literature studies. Interviews were conducted by visiting the research location directly, with 67 farmer respondents and 16 marketing institution respondents. The results of the study show that efficient marketing can be achieved when the marketing has a short marketing chain, where there are three marketing channels involving farmers, middlemen, rice mills, collectors, and retailers. The most efficient marketing criteria are found in Channels I and III, with farmer shares of 44% and 41%, respectively, and the same margin of Rp.700,000. In contrast, marketing Channel II has a margin of Rp.775,000 and farmer shares less than 40%, making it inefficient.